Clinician perceptions about inpatient occupational therapy groups in traumatic brain injury rehabilitation. (3rd July 2017) - Patterson, Freyr; Fleming, Jennifer; Doig, Emmah
ABSTRACT: Primary objective : The aim of the study was to explore the experiences and perceptions of clinicians about the benefits, challenges and processes of facilitating inpatient occupational therapy groups in traumatic brain injury (TBI) rehabilitation including peer-to-peer interactions and use of goals. Design and method : A qualitative methodology, guided by a phenomenological approach was utilized with data collected from focus groups comprising 26 clinicians working in occupational therapy in three inpatient rehabilitation settings: brain injury, spinal injury and geriatric rehabilitation in order to identify aspects unique to brain injury rehabilitation. Data were analysed using the framework analysis method. Findings : Three overarching themes emerged; 'good fit', 'the things clinicians do' and 'patient-to-patient'. Clinicians indicated that structured group formats, careful planning and communication facilitated positive group dynamics and ensured groups met individual needs. Cognitive impairments following TBI and challenging behaviours were identified to impact on group processes, and clinician skills and confidence were important in managing these. Peer-to-peer support and learning was described as a key benefit of group rehabilitation. Conclusions : Groups in TBI rehabilitation create opportunities for peer-to-peer support and learning, and contribute positively to rehabilitation but group facilitator skills are critical. Practical strategies for facilitating groups in TBI rehabilitation are suggested.